On‐Farm Yield Gains with Stress‐Tolerant Maize in Eastern and Southern Africa. (1st March 2017) - Setimela, Peter S.; Magorokosho, Cosmos; Lunduka, Rodney; Gasura, Edmore; Makumbi, Dan; Tarekegne, Amsal; Cairns, Jill E.; Ndhlela, Thokozile; Erenstein, Olaf; Mwangi, Wilfred
Abstract : Core Ideas: These selected varieties were compared with the best commercial check varieties on‐farm across 94 locations in eastern and southern Africa in a randomized complete block design with three replications for two seasons. The new drought tolerant hybrids showed a yield advantage over the commercial check varieties both in the early and medium‐late maturing categories by 4 to 19%. Among the CIMMYT hybrids, CZH0616 showed wide adaptation under stress and non‐stress conditions, making it an ideal genotype for smallholders' farmers. Under farmers' fields CZH0616, CZH0837, CZH0935, and CZH0928 were high yielding and stable across locations in eight countries that represent major maize production environments in eastern and southern Africa. Maize ( Zea mays L.) is the most important staple food in eastern and southern Africa (ESA) with human maize consumption averaging 91 kg capita −1 yr −1 . Current maize yield averages 1.2 t ha −1 and is barely sufficient for the region's requirements due to drought and low N stresses. The objective of this study was to compare new drought tolerant (DT) maize hybrids and open pollinated varieties (OPVs) against the best commercial varieties in ESA under farmer management conditions and to validate on‐station results. Maize varieties were simultaneously selected on‐station in four types of environments across 44 locations in ESA during the 2008/2009 and 2009/2010 seasons. During the 2010/2011 and 2011/2012 seasons, 20 promising DT maize hybrids and OPVs were selected from the on‐station based on their mean grain yield and stability. These selected varieties were compared with the best commercial check varieties on‐farm across 80 locations in ESA in a randomized complete block design for two seasons. The genotype + genotype × environment comparison biplot showed variety CZH0616 together with other new DT hybrids to be stable and high yielding across 44 locations on‐station in the ESA region compared to the commonly grown checks such as SC513. The new DT hybrids showed a yield advantage over the commercial check varieties both in the early and medium‐late maturing categories by 4 to 19%, and the gains were bigger under stress conditions. Under farmers' fields CZH0616, CZH0837, CZH0935, and CZH0928 were high yielding and stable across locations.